2019
DOI: 10.1111/1365-2435.13346
|View full text |Cite
|
Sign up to set email alerts
|

When is resemblance mimicry?

Abstract: Mimetic resemblance is extensive across the tree of life yet agreeing on what constitutes mimicry is challenging. One of the reasons for disagreement is a lack of unambiguous criteria to resolve whether a case of resemblance is a product of mimicry or alternative processes. Mimicry occurs when an organism takes advantage of the perception and association that a receiver has with a model to gain adaptive benefits. Three conditions should be fulfilled to confirm mimicry: (1) characterising a model, (2) identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 101 publications
(230 reference statements)
0
19
0
1
Order By: Relevance
“…The similarity in the nestling phenotypes of Vidua and their respective hosts is best explained by mimicry as supposed to any other evolutionary process. Previous work has outlined a clear set of criteria for when resemblance constitutes mimicry (de Jager and Anderson 2019) as well as laying out a series of alternative hypotheses that can generate similarity (Grim 2005). Three conditions should be fulfilled to confirm mimicry: first, the model must be identified; second, the receiver must be identified; and, third, the receiver must exert selection on the mimic to converge on the model's phenotype (de Jager and Anderson 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in the nestling phenotypes of Vidua and their respective hosts is best explained by mimicry as supposed to any other evolutionary process. Previous work has outlined a clear set of criteria for when resemblance constitutes mimicry (de Jager and Anderson 2019) as well as laying out a series of alternative hypotheses that can generate similarity (Grim 2005). Three conditions should be fulfilled to confirm mimicry: first, the model must be identified; second, the receiver must be identified; and, third, the receiver must exert selection on the mimic to converge on the model's phenotype (de Jager and Anderson 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has outlined a clear set of criteria for when resemblance constitutes mimicry (de Jager and Anderson 2019) as well as laying out a series of alternative hypotheses that can generate similarity (Grim 2005). Three conditions should be fulfilled to confirm mimicry: first, the model must be identified; second, the receiver must be identified; and, third, the receiver must exert selection on the mimic to converge on the model's phenotype (de Jager and Anderson 2019). All three conditions are met in the case of Vidua : the model is the host chick, the receiver is the host parent, and previous work has shown that chicks with mismatching mouth marking are fed less, survive worse (Payne and Payne 2002; Jamie et al.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been occasional criticism of Haskell's () system, the foundations of employing costs and benefits remain supported and unchanged (see discussion by Bronstein, ). Measuring selection strengths and directions are ideally required to confirm the existence of mimicry (de Jager & Anderson, ), but may be difficult or time consuming. As used in Haskell's () classifications, the perceived costs and benefits of protagonists may be considered as selection surrogates when exploring the evolution of mimicry.…”
Section: Costs and Benefits Associated With Different Kinds Of Mimicrymentioning
confidence: 99%
“…Several of these well-known cases of "mimicry" such as butterfly eyespots, red-black banded snakes and orchid mantises that resemble flowers are contentious. Some researchers conclude resemblance evolved via mimicry (at least in the past for some redblack banded snakes), but others instead emphasize receiver sensory bias and/or convergent evolution of the putative "models" (Bona et al, 2015;Davis Rabosky et al, 2016;Hardman et al, 2008;de Jager & Anderson, 2019;O'Hanlon et al, 2014). Conflict can also arise over definitions and semantics.…”
Section: How and Why Do Very Different Species Resemble Each Other?mentioning
confidence: 99%
“…A practical method for detecting true mimics is offered in the new paper by De Jager and Anderson (), “When is resemblance mimicry?” The authors offer a step‐by‐step guide to differentiating between true mimics, who have evolved to resemble another species in response to selection imposed by a receiver, with the consequent fitness benefits, and species that just tend to look, smell or sound similar due to other factors, particularly phylogenetic constraints, convergent evolution or chance. This significantly advances the field by focussing on the biological reality of mimicry as an evolutionary process that can be tested and confirmed experimentally, rather than on developing definitions that risk becoming outdated or restrictive.…”
mentioning
confidence: 99%